1993
DOI: 10.1620/tjem.171.153
|View full text |Cite
|
Sign up to set email alerts
|

A Case-Control Study of Colorectal Cancer and Its Relation to Diet, Cigarettes, and Alcohol Consumption in Saitama Prefecture, Japan.

Abstract: HOSHIYAMA, Y., SEKINE, T. and SASABA, T. A Case-Control Study of Colorectal Cancer and Its Relation to Diet, Cigarettes, and Alcohol Consumption in Saitama Prefecture, Japan. Tohoku J. Exp. Med., 1993, 171(2), 153-165 A case-control study of colorectal cancer in relation to dietary, smoking, and drinking habits was undertaken in Saitama Prefecture, Japan. The study was based on 181 newly diagnosed cases of adenocarcinoma of the colorectum at a single institution and 653 general population controls. Dietary hab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 29 publications
(28 reference statements)
2
54
0
1
Order By: Relevance
“…In Japan, several case-control studies have been conducted in recent years. [15][16][17]30) All but one 30) of these studies found a positive correlation between alcohol consumption and colorectal cancer. Yoshida et al showed that the risk of colon rather than rectal cancer was significantly elevated in alcohol drinkers, but sub-sites of the colon were not discriminated.…”
Section: Discussionmentioning
confidence: 99%
“…In Japan, several case-control studies have been conducted in recent years. [15][16][17]30) All but one 30) of these studies found a positive correlation between alcohol consumption and colorectal cancer. Yoshida et al showed that the risk of colon rather than rectal cancer was significantly elevated in alcohol drinkers, but sub-sites of the colon were not discriminated.…”
Section: Discussionmentioning
confidence: 99%
“…Michels et al (36) reported separate RR from two large US cohorts in their study, the Nurses' Health Study (NHS) (36a) and the Health Professionals Follow-up Study (HPFS) (36b) ; we counted the report as two prospective studies. Finally, our meta-analysis included twenty-five case-control (11,15,20,26,(28)(29)(30)(31)(33)(34)(35)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51) and sixteen cohort studies (17,19,21-25,27,32,36a,36b,37,52-55) .…”
Section: Inclusion Criteriamentioning
confidence: 99%
“…Michel et al (1996) reported that the characteristic fermentation pattern associated with the fiber from the three brown algae they investigated was attributable to the peculiar fermentation of alginates, and mannuronate was shown not to be directly involved. As for the relationship of seaweed consumption to carcinogenesis, several reports have shown preventive effects of seaweeds against colorectal carcinogenesis in epidemiological studies (Tokudome et al, 1991;Hoshiyama et al, 1993), or in experimental studies in rats (Yamamoto and Maruyama, 1985;Teas et al, 1998); proposed mechanisms for such effects include inhibition of reactive oxygen species (Maruyama et al, 2003;Suzuki et al, 2004), or the modulation of natural killer cell activity (Teas, 1983). Furthermore, there are several reports regarding the preventive effect of seaweed consumption against breast cancer (Teas, 1983;Kang et al, 2004).…”
Section: Fiber Intake Pattern S Fukuda Et Almentioning
confidence: 99%